2020
DOI: 10.7554/elife.53689
|View full text |Cite
|
Sign up to set email alerts
|

EphA7 promotes myogenic differentiation via cell-cell contact

Abstract: The conversion of proliferating skeletal muscle precursors (myoblasts) to terminally-differentiated myocytes is a critical step in skeletal muscle development and repair. We show that EphA7, a juxtacrine signaling receptor, is expressed on myocytes during embryonic and fetal myogenesis and on nascent myofibers during muscle regeneration in vivo. In EphA7-/- mice, hindlimb muscles possess fewer myofibers at birth, and those myofibers are reduced in size and have fewer myonuclei and reduced overall numbers of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Gene set enrichment analysis of EOM myogenic and non-myogenic driver genes showed that transmembrane receptor protein kinase and SMAD activity were shared terms between the two clusters, suggesting that specific complementary signaling networks could be actively maintained between these two populations ( Figure 4—figure supplement 2A ). Both signaling pathways were reported to act as inhibitors of myogenic differentiation and could therefore be associated with progenitor cell maintenance ( Arnold et al, 2020 ; Cossu et al, 2000 ). Notably, Bmpr1b and Ephb1 were among the top 100 driver genes of the myogenic EOM compartment, suggesting that myogenic commitment is associated with upregulation of these kinase receptors in the EOM ( Figure 4—figure supplement 2B , Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gene set enrichment analysis of EOM myogenic and non-myogenic driver genes showed that transmembrane receptor protein kinase and SMAD activity were shared terms between the two clusters, suggesting that specific complementary signaling networks could be actively maintained between these two populations ( Figure 4—figure supplement 2A ). Both signaling pathways were reported to act as inhibitors of myogenic differentiation and could therefore be associated with progenitor cell maintenance ( Arnold et al, 2020 ; Cossu et al, 2000 ). Notably, Bmpr1b and Ephb1 were among the top 100 driver genes of the myogenic EOM compartment, suggesting that myogenic commitment is associated with upregulation of these kinase receptors in the EOM ( Figure 4—figure supplement 2B , Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Kinase receptors have been implicated in a number of developmental programs for both muscle and associated connective tissues ( Arnold et al, 2020 ; Knight and Kothary, 2011 ; Olson and Soriano, 2009 ; Tallquist et al, 2000 ; Tzahor et al, 2003 ; Vinagre et al, 2010 ). For example, the differentiation of fetal myoblasts is inhibited by growth factors Tgfβ and Bmp4 ( Cossu et al, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even in the presence of high serum concentrations, myoblasts that have proliferated and reached confluence will spontaneously begin to differentiate, which has been described as the community effect (Arnold et al, 2020; Cossu et al, 1995; Flamini et al, 2018). We hypothesized that, upon stochastic differentiation initiation, insulin contained in the serum is one of the signals which promotes spontaneous progression towards terminal differentiation and fusion.…”
Section: Resultsmentioning
confidence: 99%
“…In other tissues such as skeletal muscle cell proliferation and differentiation are mutually exclusive processes, necessitating the involvement of stem cells (satellite cells in the skeletal muscle) to proliferate, commit, and generate post-mitotic terminally differentiated muscle cells that will fuse to form the functional unit of skeletal muscles, the myofiber ( Linkhart et al, 1981 ; Olson et al, 1991 ; Shi and Garry, 2006 ). In these contexts Ephs and ephrins most often promote cell differentiation; one example is EphA7:ephrin-A5 interaction that guides en masse skeletal muscle cell differentiation during development and regeneration ( Arnold et al, 2020 ). Table 1 (green section) and Figure 2 describe known physical interactions in cis between Ephs/ephrins and molecules regulating cell proliferation and differentiation.…”
Section: Cell Proliferation and Differentiationmentioning
confidence: 99%